Parental migration and cyberbullying victimization among Chinese left-behind children: understanding the association and mediating factors - Wang, Menmen; Lou, Jiaxue; Xie, Xiaoliang; Zhao, Guanlan; Zhu, Hui (Frontiers in Public Health, 2024)
Introduction Parental absence is greatly associated with school bullying victimization of left-behind children (LBC) in migrant families. With the increasing popularity of the Internet, little is known about the association between parental migration and cyberbullying victimization, and potential mediators. Methods We conducted a cross-sectional study in Anhui and Zhejiang Province, China, in 2020. With a sample of 792 currently left-behind children (CLBC), 541 previously left-behind children (PLBC), and 628 never left-behind children (NLBC), path analysis was used to explore the association between parental migration and cyberbullying victimization among children, while considering the independent and sequential mediating roles of parent-child communication, and time spent online. Results The prevalence of cyberbullying victimization was 29.3% among CLBC, 29.2% among PLBC, and 23.4% among NLBC. Path analysis showed that current left-behind status was positively associated with cyberbullying victimization among children (p = 0.024). Furthermore, current left-behind status was associated with worse parent-child communication, which, in turn, predicted a higher prevalence of cyberbullying victimization [95% CI = (0.007, 0.036)]. Similarly, the previous left-behind experience was associated with worse parent-child communication, which, in turn, predicted a higher prevalence of cyberbullying victimization [95% CI = (0.013, 0.043)]. Current left-behind status was associated with increased time spent online, which, in turn, predicted a higher prevalence of cyberbullying victimization [95% CI = (0.013, 0.038)]. Additionally, the current left-behind status positively predicted cyberbullying victimization among children through the serial mediating roles of parent-child communication and time spent online [95% CI = (0.001, 0.006)]. Similarly, previous left-behind experience positively predicted cyberbullying victimization among children through the serial mediating roles of parent-child communication and time spent online [95% CI = (0.002, 0.007)]. Discussion We propose that to protect CLBC and PLBC from cyberbullying victimization, it is of great importance for migrant parents to regulate children's time spent online and promote daily parent-child communication.